LANGUAGE COMPETENCE OF POLYTECHNICAL NON-ENGINEERING GRADUATES NEEDED IN THE INDUSTRY WORLD - Sri Nur Yuliyawati; Hazma (Bajang Institute, 2022)
Changes in patterns, requirements, and competition for industrial workers have caused language lectures, both Indonesian and English courses, to be encouraged to prepare graduates from polytechnic non-engineering majors to have language competencies that are in line with industry needs. For this reason, a research was conducted on